Prevalência de tracoma cicatricial em Botucatu - Estado de São Paulo - Schellini, Silvana Artioli [UNESP]; Kitakawa, Dalton [UNESP]; Onishi, Eliana [UNESP]; Hoyama, Érika; Padovani, Carlos Roberto [UNESP] (My University, 2006)
Purpose: To evaluate the prevalence of cicatricial trachoma in a population-based sample at Botucatu city-Sao Paulo State, Brazil. Methods: A population-based cross-sectional study with randomized clustered sampling of households was conducted in the urban area of the city of Botucatu, São Paulo State, Brazil. The sample was estimated in 3000 person having been appraised 2554 patient (85,1% of the intended sample) from which 2339 had more than 10 year old at the research time. All the participants were submitted to ophthalmologic examination and the data were statistical analyzed. Results: Three cicatricial trachoma carriers were detected. So, the prevalence of this affection is Botucatu city is 0,13%, affecting mainly over 40'th and having trichiasis. Conclusion: Nevertheless the low prevalence rate of cicatricial trachoma in our region, to prevent trachoma blindness is the cicatrical form of the disease is very important to treat the trichiasis.
Prevalence of trachoma in Botucatu city - Sao Paulo state
Keywords: Health surveys; Prevalence; Trachoma